Multiple capsid protein binding sites mediate selective packaging of the alphavirus genomic RNA - Rebecca S. Brown (Nature Portfolio, 2020)
Alphaviruses need to selectively package genomic viral RNA for transmission, but the packaging mechanism remains unclear. Here, Brown et al. combine PAR-CLIP with biotinylated capsid protein (Cp) retrieval and identify multiple Cp binding sites on genomic viral RNA that promote virion formation.